Mélanges - Hansay, Alfred (Hasselt : Drukkerij Léon Crollen, 1933)
Bibliotheek Camille Huysmans
Dedicator: Hansay, Alfred, dedicatee: Huysmans, Camille
Frans
Brochure
Keywords: Mantelius, Jean; lokale geschiedenis; Hasselt